Studies on transmission and life cycle of Enteromyxum scophthalmi (Myxozoa), an enteric parasite of turbot Scophthalmus maximus - Redondo, Mª José; Palenzuela, Oswaldo; Álvarez-Pellitero, Mª del Pilar (Folia Parasitologica, 2004)
In order to elucidate the transmission and dispersion routes used by the myxozoan parasite Enteromyxum scophthalmi Palenzuela, Redondo et Alvarez-Pellitero, 2002 within its host (Scophthalmus maximus L.), a detailed study of the course of natural and experimental infections was carried out. Purified stages obtained from infected fish were also used in in vitro assays with explants of uninfected intestinal epithelium. The parasites can contact and penetrate loci in the intestinal epithelium very quickly. From there, they proliferate and spread to the rest of the digestive system, generally in an antero-posterior pattern. The dispersion routes include both the detachment of epithelium containing proliferative stages to the intestinal lumen and the breaching of the subepithelial connective system and local capillary networks. The former mechanism is also responsible for the release of viable proliferative stages to the water, where they can reach new fish hosts. The finding of parasite stages in blood smears, haematopoietic organs, muscular tissue, heart and, less frequently, skin and gills, suggests the existence of additional infection routes in transmission, especially in spontaneous infections, and indicates the role of vascular system in parasite dispersion within the fish. The very high virulence of this species in turbot and the rare development of mature spores in this fish may suggest it is an accidental host for this parasite. This may also question the existence of a two-host life cycle involving an actinosporean stage in this species. Further studies are needed to clarify this open point of the life cycle. Funding for this study was provided by the EU and the Spanish Ministerio de Ciencia y Tecnología through research grants FEDER 1FD97-0679-C02-01 and AGL2001-2241-C02-01. Additional support was obtained from Stolt Sea farm S.A. We are grateful to J. Monfort for histology processing, and to research support services at the Universities of Barcelona (UB) and Valencia (UPV) for assistance in TEM ...